2015
DOI: 10.1108/jap-08-2014-0027
|View full text |Cite
|
Sign up to set email alerts
|

Abuse in care? A research project to identify early indicators of concern in residential and nursing homes for older people

Abstract: Purpose -The purpose of this paper is to contribute to the prevention of the abuse of older people in residential and nursing homes, through the identification of "early indicators of concern". Such indicators support practitioners in identifying services in which older people are at risk of abuse, neglect and ill treatment. Design/methodology/approach -Semi-structured interviews were conducted with health and social care practitioners in two local authorities (in England and Scotland), who had visited service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Such problems could move beyond the care home if they were observed by external visitors, carrying risks to reputation and regulatory status. For example, Marsland et al (2012) suggested that an early indicator of concern in care homes may be that members of staff are shouting at residents. As noted in the Serious Case Review into events at the Orchid View Care Home, there was no evidence that the care home corporate owner (Southern Cross) had equipped the manager with skills to address problems arising from the workforce diversity: The one manager in our study who reported training that was helpful had found for herself a training programme that suited her managerial imperatives and gave her a structure for minimising risks.…”
Section: Proactive Management Of Potential Conflictmentioning
confidence: 99%
“…Such problems could move beyond the care home if they were observed by external visitors, carrying risks to reputation and regulatory status. For example, Marsland et al (2012) suggested that an early indicator of concern in care homes may be that members of staff are shouting at residents. As noted in the Serious Case Review into events at the Orchid View Care Home, there was no evidence that the care home corporate owner (Southern Cross) had equipped the manager with skills to address problems arising from the workforce diversity: The one manager in our study who reported training that was helpful had found for herself a training programme that suited her managerial imperatives and gave her a structure for minimising risks.…”
Section: Proactive Management Of Potential Conflictmentioning
confidence: 99%
“…Though the "early" indicators of poor quality care in care homes that give rise to circumstances where abuse of older people is more likely to occur may well be observable and tangible, as Marsland et al (2015) asserted, such as a lack of direction and support from managers, it is also clear that such abuse remains unidentified and unreported to a significant extent, and may sometimes be deliberately concealed by the actions of care home staff (Greve, 2008;Moore, 2016b). Unfortunately, the reassurance that might otherwise arise as a result of staff holding recognised qualifications in care is illusory, because they are demonstrably over-represented among those proven to have perpetrated abuse against older people (Moore, 2017c).…”
Section: The Problem Of Imperfect Informationmentioning
confidence: 99%
“…Another example was given of "[…] a resident in an armchair be dragged forward by their head to have a cushion shoved behind their back" (focus group 2). Staff skills, knowledge and practice can be considered as an early indicator of concern (Marsland et al, 2012). However one indicator on its own is unlikely to indicate serious risk of abuse.…”
Section: Moving and Handling Issuesmentioning
confidence: 99%
“…The basic care, I have previous experience as a HCA and so could see how bad the standard of basic care was, but for a student starting with no previous experience it would have not been a good learning environment. Marsland et al (2012) found that early indicators of concern in nursing and residential homes included quality of basic care in addition to skills knowledge and practice. Therefore such issues raised by the students could be considered as early indicators of possible abuse.…”
Section: Poor Practicementioning
confidence: 99%